Lidocaine Affects Collagen Breakdown Without Compromising Cell Viability in Cultured Human Tenocytes: An In Vitro Study - Filippo Randelli; Manuel G. Mazzoleni; Alessandra Menon; Alberto Fioruzzi; Dolaji Henin; Michele Sommariva; Nicoletta Gagliano (Cells)
Local anesthetics (LAs) are frequently administered via peritendinous ultrasound-guided injections for diagnostic and therapeutic purposes. Since in vitro studies have demonstrated LAs’ tenotoxic effects, raising concerns about their safety in infiltrative treatments, and since lidocaine (LD) emerged as one of the most cytotoxic LAs, we analyzed apoptosis, oxidative stress, and collagen turnover pathways in human tenocytes treated with LD, as well as the possible protection from LD-induced injury elicited by antioxidant ascorbic acid (AA). Tenocytes from gluteal tendons were treated with 0.2 and 1 mg/mL LD, or left untreated (CT), and treated with 50 μg/mL or 250 μg/mL AA. Nuclear morphology, cytochrome c expression, and caspase 3 activation were analyzed to study the effect of LD on apoptosis. Heme Oxygenase 1 (HO-1) mRNA and genes and proteins involved in collagen turnover were investigated using molecular approaches. Our results show that 0.2 and 1 mg/mL LD did not induce apoptosis and did not modify collagen synthesis and maturation. Conversely, increased collagen degradation was observed, and AA was not protective against oxidative stress induction in the presence of LD. Our findings suggest that LD does not affect the cell viability of tenocytes and that peritendinous LD injections are safe in this regard. LD-associated collagen degradation and the AA buffer effect are still debatable. Overall, our study contributes to clarifying the effect of LD on tenocytes’ viability and ECM homeostasis and provides new additional information useful for the safe clinical application of this drug and for further analysis.